Psychological and cardiovascular effects of Guaraná and yerba mate: A comparison with coffee - Meyer, Katherine; Ball, Peter (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
An exploratory experiment was conducted to investigate the effects of coffee, guaraná, and yerba mate on mood and performance, and to determine any potential of these beverages to overcome the soporific effects of lunch. Seventy-one female students were assigned to four beverages, including a decaffeinated coffee control, and tested on two days (lunch/no lunch), over three sessions (prior to drinking the beverage, and again 60 and 150 minutes after drinking the beverages). Lunch had little effect other than to increase pulse. Guaraná increased systolic blood pressure and accuracy on a vigilance task; coffee increased accuracy on the vigilance task; but yerba mate had no significant effects. Further research is recommended before any definitive conclusions about the effects of guaraná and yerba mate are reached.